Comparison of simulation methods for electronic structure calculations with experimental electron energy-loss spectra. - Arslan, I; Ogut, S; Nellist, P; Browning, N (2003)
The electronic structure of hexagonal GaN is studied using two simulation techniques in order to develop a method to interpret the fine-structure of an experimental nitrogen K-edge electron energy loss spectrum obtained using a scanning transmission electron microscope. The application of these simulation methods to the bulk spectrum is a necessary first step in developing a fundamental understanding of the effect of changes in the electronic structure on the properties of defects. It is found here that both of the techniques used, multiple scattering (MS) and density functional theory (DFT), produce excellent agreement with the experimental bulk spectrum. The MS method is limited in accuracy but efficient in time, while the DFT method is more accurate but time consuming. Through the combination of these methods, experimental energy loss spectra can be readily understood, and a means to unravel the complexities of the electronic structure can be determined.